LINC01871 facilitates cervical cancer cell migration and immune escape by targeting miR‐873‐3p/MAP3K2 axis - Yan Li; Li Wei; Hui‐Hui Zhang; Hong‐Fei Ci; Duo‐Jie Li (Kaohsiung Journal of Medical Sciences)
Abstract Cervical cancer (CC) poses a significant threat to women's health and lives worldwide. Emerging evidence indicates that long noncoding RNA LINC01871 is closely associated with immune regulation in CC patients. However, its specific role and underlying mechanisms in CC remain poorly understood. In this study, we examined the expression levels and subcellular localization of LINC01871 in CC cell lines. Functional assays, including transwell migration and invasion assays as well as macrophage phagocytosis assays, were conducted to estimate CC cell invasiveness, migration, and immune response. Western blotting was performed to assess the protein expression of markers associated with epithelial–mesenchymal transition (EMT), immunity, and MAPK signaling. A luciferase reporter assay was used to confirm the interactions between LINC01871, miR‐873‐3p, and MAP3K2. Additionally, a xenograft mouse model was employed to investigate the in vivo effects of LINC01871 on CC progression. Our results revealed that LINC01871 is highly expressed and predominantly localized in the cytoplasm of CC cell lines. LINC01871 knockdown significantly suppressed CC cell invasion, migration, EMT, and immune escape in vitro and reduced tumor growth in vivo. Mechanistically, LINC01871 was found to interact with miR‐873‐3p, leading to the upregulation of MAP3K2 and subsequent activation of MAPK signaling. Furthermore, MAP3K2 overexpression rescued the inhibitory effects of LINC01871 silencing on the malignant behaviors of CC cells. In conclusion, LINC01871 facilitates CC metastasis by driving EMT and modulating the immune response via the miR‐873‐3p/MAP3K2/MAPK signaling pathway.